(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, proposals on the introduction of new conceptual tasks into the legislation to improve the mechanisms of ensuring a reliable guarantee of individual rights and freedoms in criminal procedure legislation are scientifically based.